Pengaruh penyuluhan menggunakan media lembar balik tentang buah dan sayur pada siswa sekolah dasar - Fera Ratnasari; Arnisam Arnisam (Poltekkes Kemenkes Aceh, 2023)
Background: The prevalence of fruit and vegetable consumption among school-aged children In Indonesia is approximately 96%. A lack of fruit and vegetable consumption can lead to a decreased immune system, increase the risk of constipation, cancer, and obesity, and reduce human resource productivity. Therefore, elementary school students' knowledge of nutrition, especially fruits and vegetables, needs to be improved by providing nutrition education on the importance of fruit and vegetable consumption.Objectives: To determine the effect of counseling using flip sheet media on increasing elementary school student’s knowledge of the importance of fruit and vegetable consumption in elementary school children.Methods: The research model used two stages. The first stage uses a media development design (R&D), and the second uses a quasi-experimental approach. The sample comprised of 44 participants. This research was conducted at SDN 62 in Banda Aceh, Lueng Bata District, Banda Aceh City. This study was conducted between April and May 2023. Data collection included primary and secondary data processed through editing, coding, processing, and cleaning. Data analysis was performed using a Dependent T-test at a 95% confidence interval (CI).Results: Counseling increased the children's knowledge of the importance of fruit and vegetable consumption (p= 0,006). The average knowledge of students before being given counseling using the flip sheet media was 64,55 + 8,19. Then, after being given counseling, the average value of knowledge increased to 96,02 + 4,39.Conclusion: Counseling using flip-sheet media affected children's knowledge of the importance of fruit and vegetable consumption.